2020
DOI: 10.1029/2019gh000222
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Hair Mercury Levels Are Associated With Neurodevelopmental Deficits in Children Living Near Artisanal and Small‐Scale Gold Mining in Peru

Abstract: Children living near artisanal and small-scale gold mining (ASGM) are at risk of exposure to mercury, a neurotoxicant. It is not certain whether such exposures are harming development, as they occur in underresourced contexts entwined with other stressors, such as malnutrition and enteric infection.This study sought to investigate the association between hair-mercury levels and visual-motor, cognitive, and physical development among children living near ASGM in the Peruvian Amazon. Total hair-mercury levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 59 publications
2
26
0
2
Order By: Relevance
“…Studies have associated prenatal MeHg exposure with cognitive delays and mild mental retardation [6,54,55]. Reuben et al [56] observed loss of cognitive ability in ASGM mercury-exposed children in the Peruvian Amazon. In Brazil, Marques et al [57,58] identified psychomotor alterations and mental development problems in children from Rondônia state, in the Amazon region.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have associated prenatal MeHg exposure with cognitive delays and mild mental retardation [6,54,55]. Reuben et al [56] observed loss of cognitive ability in ASGM mercury-exposed children in the Peruvian Amazon. In Brazil, Marques et al [57,58] identified psychomotor alterations and mental development problems in children from Rondônia state, in the Amazon region.…”
Section: Introductionmentioning
confidence: 99%
“…The cohort studies conducted in the Faroe Islands and New Zealand indicate that even in low doses, the consumption of mercury-contaminated fish during pregnancy can cause important cognitive alterations in children [48,49]. The mercury neurotoxic potential effects in children and adults of the Amazon have been reported in recent publications [50][51][52][53][54]. The most common effects in children are cognitive problems, neurodevelopmental impairment, and psychomotor disorders.…”
Section: Discussionmentioning
confidence: 99%
“…While economic differences may partially explain higher anemia prevalence in indigenous communities, additional efforts are needed to assess why anemia rates in indigenous communities remain higher than those in non-indigenous communities. Recent studies have shown indigenous communities to have significantly higher levels of mercury that often surpass World Health Organization's guidelines, and have been associated with lower hemoglobin levels [9,20,24]. Lack of effective medical access, poor nutrition, enteric disease or other unknown factors may also play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Data on anemia and hemoglobin levels collected prior to 2017 are from four studies by our team: the 2014 Interoceanic Highway and River studies ; the Amarakaeri Reserve Cohort study (2015 baseline and 2016 Follow Up ); and the Knowledge, Attitudes and Practices of Mercury Exposure study in 2017 [9,[15][16][17][18][19][20]. The design of each of these studies varied slightly, but the data collection instruments were similar and every person living in an enrolled household was offered an anemia test using a Hemocue Hb201+ (HemoCue®), following the same protocols across studies-standardization at the start and midpoint of each study using control blood samples provided by the manufacturer.…”
Section: B Data Collectionmentioning
confidence: 99%